Adhesive composition for hot press molding, method for producing hot press molded article, and hot press molded article
The adhesive composition combining polyisocyanate and high β-O-4 bond lignin residues enhances the strength and water resistance of thermocompression molded bodies, overcoming the limitations of lignin recycling and reuse in thermocompression molding.
Patent Information
- Application Number
- JP2023178915
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-30
AI Technical Summary
The strength and water resistance of thermocompression molded bodies made from lignin materials are significantly reduced, posing challenges for recycling and reuse of lignin in thermocompression molding processes.
An adhesive composition for thermocompression molding is developed, comprising polyisocyanate and lignin residues from ethanol production, which includes lignin with a high β-O-4 bond amount. This composition forms a networked binder when heat-pressed, enhancing the strength and water resistance of the molded bodies.
The use of the adhesive composition results in thermocompression molded bodies with sufficient strength and water resistance, effectively addressing the recycling and reuse challenges associated with lignin materials.
Smart Images

Figure 2025068860000001 
Figure 2025068860000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition for hot-press molding, a method for producing a hot-press molded article, and a hot-press molded article. [Background technology]
[0002] One known method for manufacturing wood boards made from lignocellulosic materials such as wood chips and wood fibers is to mix the base material with a binder such as an adhesive and then thermocompress the mixture (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-86817 A Summary of the Invention [Problem to be solved by the invention]
[0004] When recycling wood-based materials such as residues generated at paper mills and waste building materials, thermal recycling, which consumes them as fuel, has been widely used. However, in recent years, from the perspective of CO2 fixation, reuse through material recycling has been attracting attention.
[0005] However, when the inventors investigated the use of lignin, such as lignin sulfonic acid obtained in the papermaking process, as a material for thermo-pressed compacts, they found that the strength and water resistance of the thermo-pressed compacts could be significantly reduced, making it clear that there are issues with recycling lignin as a material.
[0006] An object of the present invention is to provide an adhesive composition for hot-press molding, which can provide a hot-press molded article having sufficient strength and water resistance by material recycling of lignin, and a method for producing the hot-press molded article.An object of the present invention is to provide a hot-press molded article having sufficient strength and water resistance by material recycling of lignin. [Means for solving the problem]
[0007] In some aspects, the present invention provides the following [1] to
[12] .
[0008] [1] A thermocompression molding adhesive composition comprising a polyisocyanate and lignin, a residue from the production of ethanol from cellulosic biomass. [2] The adhesive composition for hot-press molding according to [1], wherein the ethanol production residue lignin contains lignin having a β-O-4 bond amount of 40 μmol / g or more. [3] The adhesive composition for hot-press molding according to [1] or [2], wherein the polyisocyanate comprises a modified polyisocyanate obtained by reacting a polymethylene polyphenyl polyisocyanate compound with a polyether compound containing an average of five or more oxyethylene units per molecule and having a hydroxyl group. [4] The adhesive composition for hot-press molding according to [3], wherein the polyether compound contains 80 mass% or more of oxyethylene units and has an average functional number of hydroxyl groups per molecule of 1.5 or less. [5] The adhesive composition for hot and press molding according to any one of [1] to [4], further comprising a curing accelerator. [6] The adhesive composition for hot-press molding according to [5], wherein the curing accelerator is an aliphatic tertiary amine compound. [7] The adhesive composition for hot-press molding according to [5], wherein the curing accelerator is an aliphatic tertiary amine compound having an active hydrogen group. [8] The adhesive composition for hot-press molding according to any one of [5] to [7], wherein the content of the curing accelerator is 0.25 to 10 parts by mass per 100 parts by mass of the polyisocyanate. [9] A method for producing a thermocompression molded product, comprising hot pressing a thermocompression molding precursor comprising a substrate and the thermocompression molding adhesive composition according to any one of [1] to [8].
[10] The method for producing a hot-press molded product according to [9], wherein the content of the ethanol production residue lignin in the hot-press molded precursor is 1 to 10 parts by mass per 100 parts by mass of the base material.
[11] The method for producing a hot-press molded body according to [9] or
[10] , wherein the base material is a lignocellulosic material.
[12] The method for producing a hot-press molded product according to any one of [9] to
[11] , wherein the hot-press molded precursor is obtained by applying a second agent containing a component other than the components of the first agent of the adhesive composition to a composite material containing the base material and a first agent of the adhesive composition containing the ethanol production residue lignin.
[13] A hot-press molded product obtained by hot-pressing a hot-press molding precursor comprising a substrate and the hot-press molding adhesive composition according to any one of [1] to [8]. Effect of the Invention
[0009] According to one aspect of the present invention, there is provided an adhesive composition for hot-press molding, which allows a hot-press molded article having sufficient strength and water resistance to be obtained by material recycling of lignin, and a method for producing a hot-press molded article. According to another aspect of the present invention, there is provided a hot-press molded article having sufficient strength and water resistance to be obtained by material recycling of lignin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, exemplary embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments. In this specification, a numerical range indicated using "~" indicates a range including the numerical values before and after "~" as the minimum and maximum values, respectively. In addition, unless specifically stated otherwise, the units of the numerical values before and after "~" are the same. In addition, the upper limit value and the lower limit value described individually can be arbitrarily combined.
[0011] <Adhesive composition for thermocompression molding> The hot-press molding adhesive composition of the present embodiment contains polyisocyanate and lignin that is a residue from the production of ethanol from cellulosic biomass.
[0012] According to the adhesive composition for thermocompression molding of the present embodiment, a thermocompression molded body having sufficient strength and water resistance can be obtained by material recycling of lignin. The inventors speculate as follows about the reason for obtaining such an effect. For example, when a base material constituting a thermocompression molded body is mixed with lignin, and polyisocyanate is applied thereto and then hot-pressed, it is considered that in the thermocompression molded body formed, lignin functions as a wood base material while reacting with the isocyanate group of the polyisocyanate to form a networked binder. Here, when the lignin is ethanol production residue lignin, it is considered that the binder is polymerized and highly crosslinked due to the inclusion of many β-O-4 bonds formed by the lignin intermolecular polymerization reaction, and the content of sulfur-containing functional groups is sufficiently small, thereby suppressing the decrease in strength and water resistance that occurred when lignin such as lignin sulfonic acid was used.
[0013] The adhesive composition for hot-press molding may be a one-component type (e.g., one-liquid type) composition in which all of the components are contained in one agent, or a multi-component type (e.g., two-liquid type) composition in which the components are separated into multiple agents. For example, the adhesive composition for hot-press molding may include a first agent containing lignin, a residue of ethanol production from cellulosic biomass, and a second agent containing polyisocyanate. In this case, the first agent containing lignin, a residue of ethanol production from cellulosic biomass, and the substrate may be mixed, and then the second agent containing polyisocyanate and other components (e.g., curing accelerator, etc.) may be applied.
[0014] (Polyisocyanate) The polyisocyanate is a compound having a plurality of isocyanate groups. Examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, lysine diisocyanate, triphenylmethane triisocyanate, tetramethylxylene diisocyanate, 1,6- Examples of the isocyanate include hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, lysine ester triisocyanate, 1,6,11-undecane triisocyanate, 1,8-diisocyanate-4-isocyanate methyl octane, 1,3,6-hexamethylene triisocyanate, bicycloheptane triisocyanate, and trimethylhexamethylene diisocyanate. In addition, modified products of these polyisocyanates (urethane modified products, carbodiimide modified products, allophanate modified products, urea modified products, biuret modified products, isocyanurate modified products, amide modified products, imide modified products, uretonimine modified products, uretdione modified products, or oxazolidone modified products) and condensates of these isocyanates (polymethylene polyphenylene polyisocyanate compounds, etc.) can also be used.
[0015] As the polyisocyanate, from the viewpoint of further improving water resistance while maintaining the strength of the thermocompression molded body, it is preferable to use polymeric MDI, which is a mixture of diphenylmethane diisocyanate (MDI) and diphenylmethane diisocyanate-based polynuclear condensation product (MDI-based condensation product). From the same viewpoint, MDI and a modified MDI (urethane modified, carbodiimide modified, allophanate modified, urea modified, biuret modified, isocyanurate modified, amide modified, imide modified, uretonimine modified, uretdione modified, or oxazolidone modified) may be used in combination, or polymeric MDI and a modified MDI (urethane modified, carbodiimide modified, allophanate modified, urea modified, biuret modified, isocyanurate modified, amide modified, imide modified, uretonimine modified, uretdione modified, or oxazolidone modified) may be used in combination.
[0016] The polyisocyanate may contain a modified polyisocyanate obtained by reacting a polymethylene polyphenylene polyisocyanate compound such as polymeric MDI with a polyether compound containing an average of 5 or more oxyethylene units per molecule and having a hydroxyl group. In this case, the viscosity is reduced and the volume is increased by forming an emulsion with water, which improves the dispersibility in the substrate, and it becomes easy to improve the water resistance while maintaining the strength of the thermocompression molded product.
[0017] The NCO content in the modified polyisocyanate may be 20 to 33.5% by mass.
[0018] The polyether compound may contain 80% by mass or more, or 85% by mass or more of oxyethylene units from the viewpoint of the ability and properties of the modified polyisocyanate to form an emulsion with water. The polyether compound may have an average functional number of hydroxyl groups per molecule of 1.5 or less, or 1.1 or less from the viewpoint of the liquid properties such as the viscosity of the modified polyisocyanate.
[0019] Examples of polyether compounds include polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol, which have 1 to 5 functional groups and a number average molecular weight of 300 to 10,000, obtained by ring-opening polymerization of ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, or the like using an initiator described below, and polyether polyols obtained by copolymerizing these. In this specification, polyether polyol includes monools, and alkoxy polyoxyethylene glycols are also included in polyether polyols.
[0020] Further, examples of the polyether compound include known polyester polyols and polyester ether polyols using polycarbonate polyols as initiators.
[0021] Examples of the initiator include various monoalcohols, glycols, glycol ethers, monoamines, diamines, aminoalcohols, water, and urea having a functional group number of 1 to 5 and a number average molecular weight of 18 to 500. The initiators may be used alone or in combination of two or more.
[0022] The above polyether compounds may be used alone or in combination of two or more.
[0023] (Cure accelerator) The adhesive composition for hot-press molding of the present embodiment may further contain a curing accelerator to promote reaction curing between the polyisocyanate and the lignin from the ethanol production residue (if the substrate has a hydroxyl group, further reaction curing with the substrate). In this case, it becomes easy to improve the physical properties (e.g., bending strength and water resistance) of the hot-press molded product by forming a network between the polyisocyanate and the lignin from the ethanol production residue (if the substrate has a hydroxyl group, further network formation with the substrate).
[0024] Examples of the curing accelerator include known urethane catalysts such as tertiary amine catalysts, amine catalysts having a hydroxyl group, and metal catalysts. The curing accelerator may be used alone or in combination of two or more.
[0025] Examples of tertiary amine catalysts include ethylenediamine, diethylenetriamine, triethylamine, triethylenediamine, N-methylmorpholine, N-methylimidazole, 1-methylimidazole, 1-ethylimidazole, 1-propylimidazole, 1-cyanoimidazole, 1-cyanomethylimidazole, 1,2-dimethylimidazole, 1,4-dimethylimidazole, 1-methyl-2-ethylimidazole, 1-methyl-4-ethylimidazole, 1-ethyl-2-methylimidazole, 1-ethyl-4-methylimidazole, pyridine, and α-picoline.
[0026] Examples of amine catalysts having a hydroxyl group include monoethanolamine, diethanolamine, triethanolamine, N,N-dimethylethanolamine, N,N-dimethylhexanolamine, N,N,N'-trimethylaminoethylethanolamine, and N,N,N',N'-tetramethylhydroxypropylenediamine.
[0027] Examples of the metal catalyst include dibutyltin dilaurate, dioctyltin dilaurate, calcium naphthenate, potassium octoate, tin octoate, and zinc octoate.
[0028] Among the above, aliphatic tertiary amine compounds are preferred, and since reactive catalysts are capable of suppressing emission from the molded body after thermocompression molding, active hydrogen group-containing aliphatic tertiary amine compounds are more preferred, and hydroxyl group-containing aliphatic tertiary amines are particularly preferred.
[0029] In the present embodiment, from the viewpoint of ease of adjusting the curing time, the tertiary amine catalyst may be an aliphatic tertiary amine compound such as ethylenediamine or diethylenetriamine, or an aliphatic tertiary amine compound having an active hydrogen group. Examples of the aliphatic tertiary amine compound having an active hydrogen group include diethanolamine and triethanolamine.
[0030] The content of the curing accelerator in the thermocompression molding adhesive composition may be 0.1 to 15 parts by mass, 0.5 to 12 parts by mass, or 1.0 to 10 parts by mass, relative to 100 parts by mass of the polyisocyanate. When the content of the curing accelerator is within such a range, it becomes easy to form a network between the polyisocyanate and the lignin remaining after ethanol production (and further form a network with the substrate when the substrate has a hydroxyl group) and to adjust the reactivity in the production process.
[0031] (Lignin from ethanol production residue from cellulosic biomass) As the residual lignin from ethanol production from cellulosic biomass (hereinafter sometimes referred to as "ethanol production residual lignin"), the lignin obtained as a residue from solid-liquid separation of the saccharification fermentation liquid when producing ethanol from cellulosic biomass can be used. In the bioethanol production process, cooking using alkali or chemicals as in the pulp production process is not performed, and water-soluble components are transferred to the water side in the solid-liquid separation process, so that a lignin residue with few chemical impurities can be obtained.
[0032] Examples of plant resources for producing bioethanol include sugarcane bagasse, corn (cobs, stems and leaves, and residues such as corn stover), sorghum, sweet sorghum, switchgrass, erianthus, napier grass, and other grasses.
[0033] In general, herbaceous plant resources contain 40-50% cellulose, 15-25% hemicellulose, and 20-30% lignin. For example, the cellulose and hemicellulose in herbaceous plant resources can be hydrolyzed to produce glucose, and the glucose obtained can be fermented to produce bioethanol. The residue components separated from the obtained bioethanol by water extraction contain water-insoluble lignin and sugars.
[0034] The method for producing bioethanol may include a step of hydrolyzing cellulose and hemicellulose of plant flour using a catalyst. This allows oligosaccharides including glucose and xylose, and cellulose to be obtained as hydrolysates. The temperature of hydrolysis may be 150°C or higher and lower than 200°C. There is no particular limitation on the catalyst as long as it decomposes or softens lignin and decomposes cellulose and hemicellulose, and examples of the catalyst include sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, sodium hydroxide, potassium hydroxide, ammonia, and the like. These may be used alone or in combination. Among them, sulfuric acid can be used for industrial use from the viewpoint of low cost and easy availability.
[0035] The hydrolysate obtained in the above steps can be further subjected to a step of saccharification using an enzyme and / or fermentation using a microorganism to obtain bioethanol. The enzyme may be any enzyme capable of decomposing hemicellulose and cellulose contained in a grass family plant into monosaccharide units, and examples of the enzyme include those having cellulase and hemicellulase activities. The microorganism is not particularly limited as long as it can produce a fermentation product derived from the stems and leaves of a grass family plant, and examples of the microorganism include yeast and bacteria. The microorganism may be a genetically modified microorganism.
[0036] The produced bioethanol can be separated from the fermentation liquor by extraction with water, and the residue of the fermentation liquor after the bioethanol has been extracted with water may be dried to produce a powder.
[0037] The lignin content in the ethanol production residue lignin may be 50 to 70 mass % or 55 to 65 mass % from the viewpoint of functionality. The lignin content is determined by the Klason lignin method.
[0038] The amount of β-O-4 bonds in the lignin from the residue of ethanol production may be 40 μmol / g or more, or may be 40 to 350 μmol / g, from the viewpoint of functionality. The amount of β-O-4 bonds is determined by the thioacidolith method.
[0039] From a practical standpoint, the ethanol production residue lignin may have a detectable amount of sulfur components of 0.1% or less in elemental analysis.
[0040] From the viewpoint of functionality, the molecular weight of the lignin in the ethanol production residue lignin may be a number average molecular weight (Mn) of 2,000 to 4,500 as measured by GPC.
[0041] The thermocompression molding adhesive composition of the present embodiment may contain other additives such as a wax emulsion, if necessary.
[0042] The adhesive composition for hot-press molding of the present embodiment may contain a solvent such as water, acetone, ethyl acetate, or methyl ethyl ketone. For example, when the adhesive composition for hot-press molding contains a first agent containing ethanol production residue lignin and a second agent containing polyisocyanate, the second agent may contain the above-mentioned solvent. In addition, when the second agent contains the above-mentioned modified polyisocyanate and water, the viscosity is reduced and the volume is increased by forming an emulsion with water, thereby improving the dispersibility in the substrate. In this case, the second agent may be prepared so that the mass ratio of the modified polyisocyanate to water [modified polyisocyanate / water] is 60 / 40 to 40 / 60.
[0043] The amount of polyisocyanate in the thermocompression molding adhesive composition of this embodiment may be 1 to 25 parts by mass, 3 to 20 parts by mass, or 5 to 15 parts by mass relative to 100 parts by mass of the total mass of the base material and the ethanol production residue lignin of the thermocompression molded body to be formed.
[0044] The amount of the lignin residue from ethanol production in the adhesive composition for hot-press molding of this embodiment may be 0.5 to 20 parts by mass, 2.0 to 15 parts by mass, or 4 to 9 parts by mass, relative to 100 parts by mass of the total mass of the base material and the lignin residue from ethanol production of the hot-press molded body to be formed.
[0045] <Method of manufacturing hot-press molded body> The method for producing a thermocompression molded product of the present embodiment includes a step of hot pressing a thermocompression molding precursor that includes a substrate and the above-described thermocompression molding adhesive composition of the present embodiment.
[0046] In the method for producing a thermocompression molded product of the present embodiment, the above-mentioned thermocompression molded precursor may be prepared by applying a second agent containing a component other than the components of the first agent of the thermocompression molding adhesive composition of the present embodiment to a composite material containing a substrate and a first agent containing ethanol production residue lignin of the thermocompression molding adhesive composition of the present embodiment. In this case, the production method may include a composite material preparation step, an adhesive application step, and a heat pressing step.
[0047] (Composite preparation process) In this step, a composite material can be prepared by mixing a substrate with the first agent containing the ethanol production residue lignin of the thermocompression molding adhesive composition of this embodiment.
[0048] Lignocellulosic materials such as wood chips and wood fibers can be used as the substrate. Examples of lignocellulosic materials include strand chips, dust chips, and flake chips, which are wood chips used in particle board, oriented strand board (OSB), wafer board, laminated veneer lumber (LVL), laminated strand lumber (LSL), parallel strand lumber (PSL), etc.; fibers used in hardboard, medium density fiberboard (MDF), insulation board, etc.; sorghum stalks, bagasse, rice husks, hemp, straw, rush grass, reeds, coconut and tree, rubber tree, corn, sawdust, etc. These may be used alone or in combination of two or more.
[0049] The substrate may be prepared by converting the above-mentioned raw material into small pieces, fibers, or powder using a known chipper, flaker, knife ring shredder, refiner, etc. In this embodiment, in order to ensure the homogeneity of the thermocompression molded body, a fine substrate, which is a substrate classified with an opening size of 4 mm to 0.15 mm, can be used.
[0050] The first agent containing ethanol production residue lignin may contain inorganic fillers such as cement, blast furnace slag, gypsum, calcium carbonate, clay, aluminum hydroxide, antimony trioxide, quicklime, hydrated lime, and bentonite, as well as leveling agents, flame retardants, antiaging agents, heat resistance agents, and antioxidants.
[0051] Examples of the method for mixing the base material and the first agent include a central stirring method, a side stirring method, and an air current stirring method.
[0052] The mixing ratio of the base material and the first agent may be adjusted to 0.5 to 20 parts by mass, 2 to 15 parts by mass, or 4 to 9 parts by mass, relative to 100 parts by mass of the total mass of the base material and the ethanol production residue lignin.
[0053] (Adhesive application process) In this step, a second agent containing components other than the components of the first agent of the thermocompression molding adhesive composition of this embodiment may be applied to the composite obtained in the composite preparation step.
[0054] As a method for applying the second agent to the composite material, any known means (e.g., a blender, a batch-type horizontal ribbon blender, a planetary mixer, a Henschel mixer, etc.) can be used as long as it is a method that can adhere the components of the second agent, such as polyisocyanate, to the surfaces of the base material and the ethanol production residue lignin contained in the composite material. For example, a predetermined amount of the second agent may be supplied to a blender to which a predetermined amount of the composite material has been supplied, and then mixed and stirred.
[0055] The method of supplying the second agent to the blender may, for example, be to add the second agent as is, or to spray the liquid second agent in a mist form. In this case, it may be sprayed as an emulsion with water adjusted to a solids content of 40 to 60 mass %.
[0056] The blending ratio of the composite material and the second agent may be adjusted so that the mass of the polyisocyanate is 1 to 25 parts by mass, 3 to 20 parts by mass, or 5 to 15 parts by mass relative to 100 parts by mass of the total mass of the base material and the lignin residue from ethanol production.
[0057] (Heat pressing process) In this step, the thermocompression molding precursor containing the substrate and the thermocompression molding adhesive composition of the present embodiment obtained through the above steps can be heat-pressed.
[0058] The hot-press molding precursor may be a molded product (such as a sheet-like mat) obtained by pre-compressing the composite material coated with the second agent obtained in the adhesive application step into a predetermined shape.
[0059] As a method of heat pressing, a known heat press machine may be used to heat press the heat press molding precursor from above and below with hot plates. The pressing temperature may be 100 to 270°C, 140 to 250°C, or 160 to 200°C. The pressing pressure may be 1 to 8 MPa, 1.5 to 6 MPa, or 2 to 4 MPa. The pressing time (per mm thickness) may be 6 to 60 seconds, 8 to 30 seconds, or 10 to 20 seconds.
[0060] Through the above-mentioned steps, a thermocompression molded body is obtained. EXAMPLES
[0061] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0062] <Ingredient preparation> As materials used in the examples and comparative examples, the following base material, lignin, polyisocyanate, and curing accelerator were prepared.
[0063] [Base material] Substrate 1: Wood chips (crushed building materials, passed through a 2 mm mesh, moisture content 2% by mass)
[0064] [Lignin] Lignin 1: Ethanol production residue lignin prepared by the following method (sugar content: 30-40% by mass, average particle size: 50 μm) Herbaceous biomass pretreated by dilute sulfuric acid cooking was enzymatically saccharified, and the resulting saccharification product was added with yeast for fermentation. The resulting fermentation product was then separated into an aqueous solution and a solid fraction, and the solid fraction was dried. Lignin 2: "L0082 Sodium lignosulfonate (alkaline lignin)" (Tokyo Chemical Industry Co., Ltd., product name)
[0065] Lignin 1 is composed mainly of lignin decomposed by dilute sulfuric acid cooking, and does not substantially possess sulfo group chemical modifications like Lignin 2, which is composed mainly of lignosulfonic acid discharged as a by-product from the papermaking process, and has a low sulfur content.
[0066] (Lignin Analysis) The following table summarizes (a) the lignin content measured by the Klason lignin method, (b) the amount of β-O-4 bonds measured by the thioacidoris method, (c) the detection of sulfur components by elemental analysis, and (d) the number average molecular weight (Mn) measured by GPC. [Table 1]
[0067] [Polyisocyanate] Water-emulsified MDI binder 1: Self-emulsifying polyisocyanate prepared by the method below. A 2,000 ml reactor equipped with a stirrer, a thermometer, a cooler, and a nitrogen gas inlet tube was charged with 970 g of polyisocyanate (Millionate MR-200, product name, manufactured by Tosoh Corporation) and 30 g of MPEG-400 (product name, manufactured by Toho Chemical Industry Co., Ltd.), and the temperature was raised to 80°C and the reaction was carried out for 3 hours to prepare water-emulsified MDI binder 1.
[0068] [Cure accelerator] Curing accelerator 1: "TOYOCAT-A30" (product name, manufactured by Tosoh Corporation)
[0069] <Preparation of hot-pressed compact> Example 1 532 g (95 parts by mass) of wood chips as the substrate and 28 g (5 parts by mass) of Lignin 1 as the first agent were placed in a blender equipped with a stirring blade, and while stirring and mixing, a second agent containing an emulsion of 55 g (10 parts by mass) of water-emulsified MDI binder 1 and 1.37 g (0.25 parts by mass) of hardening accelerator 1 emulsified in 88 g of water (added water for adjusting the moisture content so that the final moisture content would be 14% by mass) was added, and a composite material coated with the second agent was obtained.
[0070] The composite material coated with the second agent was evenly spread inside a wooden frame (300 mm x 300 mm) and pre-compressed, after which the wooden frame was removed to obtain a mat (moisture content 14% by mass). Next, SUS-304 test panels were placed on the top and bottom of the mat, and hot-pressed under conditions of a press temperature of 180°C, a maximum surface pressure of 3.0 MPa, and a hot-press time of 150 seconds to obtain a 10 mm thick hot-pressed compact (density 0.7 g / cm). 3 ) was obtained.
[0071] (Examples 2 to 4) A hot-press molded article was obtained in the same manner as in Example 1, except that the amounts of the base material and the first agent were changed to those shown in Table 2.
[0072] Example 5 A hot-press molded product was obtained in the same manner as in Example 1, except that no curing accelerator was added.
[0073] Comparative Example 1 A hot-pressed compact was obtained in the same manner as in Example 1, except that Lignin 2 was used instead of Lignin 1.
[0074] <Evaluation of hot-pressed molded products> The thermocompression molded products obtained in the examples and comparative examples were measured for their physical properties (water absorption rate, water absorption thickness expansion rate, bending strength) in accordance with JIS-A5908. The water absorption thickness expansion rate was measured by a 70°C, 2-hour immersion test (conditions equivalent to the JIS-A5908 wet bending strength A test). The results are shown in Table 2.
[0075] [Table 2]
Claims
1. A hot-press molding adhesive composition comprising a polyisocyanate and lignin, a residue from the production of ethanol from cellulosic biomass.
2. The adhesive composition for hot-press molding according to claim 1, wherein the ethanol production residue lignin contains lignin having a β-O-4 bond amount of 40 μmol / g or more.
3. 2. The adhesive composition for hot-press molding according to claim 1, wherein the polyisocyanate comprises a modified polyisocyanate obtained by reacting a polymethylene polyphenyl polyisocyanate compound with a polyether compound containing an average of 5 or more oxyethylene units per molecule and having a hydroxyl group.
4. The adhesive composition for hot-press molding according to claim 3 , wherein the polyether compound contains 80 mass % or more of oxyethylene units and has an average functional number of hydroxyl groups per molecule of 1.5 or less.
5. The hot press molding adhesive composition according to claim 1 , further comprising a curing accelerator.
6. The adhesive composition for hot press molding according to claim 5 , wherein the curing accelerator is an aliphatic tertiary amine compound.
7. The adhesive composition for hot-press molding according to claim 5 , wherein the curing accelerator is an aliphatic tertiary amine compound having an active hydrogen group.
8. The adhesive composition for hot-press molding according to claim 5, wherein the content of the curing accelerator is 0.25 to 10 parts by mass per 100 parts by mass of the polyisocyanate.
9. A method for producing a hot-press molded product, comprising hot-pressing a hot-press molding precursor comprising a substrate and the hot-press molding adhesive composition according to any one of claims 1 to 8.
10. The method for producing a hot-press molded body according to claim 9, wherein the content of the ethanol production residue lignin in the hot-press molded precursor is 1 to 10 parts by mass relative to 100 parts by mass of the base material.
11. The method for producing a hot-pressed compact according to claim 9 , wherein the substrate is a lignocellulosic material.
12. 10. The method for producing a hot-press molded body according to claim 9, wherein the hot-press molded precursor is obtained by applying a second agent containing a component other than the components of the first agent of the adhesive composition to a composite material containing the base material and a first agent of the adhesive composition containing the ethanol production residue lignin.
13. A thermocompression molded article obtained by hot pressing a thermocompression molding precursor comprising a substrate and the thermocompression molding adhesive composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Manufacturing method of medium density fiberboard
JP2018086817A